Synthesis and biological evaluation of simplified analogs of lophocladine B as potential antitumor agents - Sewan Theeramunkong (2018)
© 2016, Springer Science+Business Media New York. In this study, two series of simplified isoquinolines deriving from lophocladine B were synthesized and evaluated for their antitumor activity. Suzuki-Miyaura and Sharpelss-Fokin reactions were employed to synthesize 26 compounds. Two compounds (25 and 27) showed to be cytotoxic with IC50 values of 10 µM on hepatic cancer cells and 13 µM on cervical cancer cells, respectively. Further studies on their mechanism of action showed that compound 27 mediated cytotoxicity through apoptosis induction.